Cost of illness in Charcot-Marie-Tooth neuropathy: Results from Germany. (23rd April 2019) - Schorling, Elisabeth; Thiele, Simone; Gumbert, Laura; Krause, Sabine; Klug, Constanze; Schreiber-Katz, Olivia; Reilich, Peter; Nagels, Klaus; Walter, Maggie C.
Abstract : Objective: To assess cost associated with the disease-specific need of patients diagnosed with Charcot-Marie-Tooth neuropathies (CMT) in Germany. Methods: Patients with CMT were identified through the national patient registry and invited to complete a standardized questionnaire. The data collected include information about health care use, informal care, and other disease-related expenses as well as the working situation. Based on this information, we estimated the annual cost of CMT from the perspective of society. Results: This study included 397 patients with a genetically confirmed CMT diagnosis. We estimated total annual cost of illness (COI) of $22, 362 (95% CI $19, 464–$25, 723) per patient, of which 67.3% were direct costs. The highest single cost factor was informal care cost. For Germany, we extrapolated total cost of CMT of $735.0 million ($639.8 million–$845.5 million). Multivariate regression analysis showed that total annual cost increased with disease severity (Charcot-Marie-Tooth Neuropathy Score). Age, CMT subtype, comorbidities, body mass index, and employment status were also predictors of a change in cost ( p < 0.05). Moreover, we found differences in total cost depending on marital status, subjectively evaluated impairments, dependence on other persons, care level, educational level, and disease duration. Conclusions: CMT is associated with a substantial economic burden. For the first time, the COI of CMT has been assessed and will serve as important input to decision-making in health policy, especially regarding research and development of therapies. Moreover, our results indicate the importance of the patient-reported perception of disease severity related to the consumption of resources.